Kepemimpinan, Kepuasan Kerja, dan Komitmen Organisasi - Asep Hidayat; Endiana Endiana; John Chaidir (Amal Insani Foundation, 2023)
Leadership has a significant role in various aspects of life, whether in organizations, society, or the intimate environment. Effective leadership involves the ability to direct and manage a team properly. A leader can identify individual strengths and weaknesses in a group and allocate tasks and responsibilities efficiently. In this ever-evolving era, innovation and adaptation to change are very important for the survival of an organization or society. A leader can explore new ideas, encourage creativity, and create an environment that supports innovation. They are also able to manage change well, design appropriate strategies, and guide people through transitions that can be difficult. This study comprehensively discussed the relationship between leadership, job satisfaction, and organizational commitment.